Theoretical risk assessment of food colorants approved in China - GE Jianhong; WEI Xuetao; XIAO Xiao; XU Haibin; YANG Dajin; QU Pengfeng; YONG Ling; SONG Yan (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo carry out the theoretical risk assessment for food colorants in the National food safety standard-standards for uses of food additives (GB 2760—2014) by Budget method and deterministic assessment.MethodsBudget method was applied for calculating the theoretical maximum daily intake of food colorants which had ADI values and maximum use levels. For the additives whose intakes were higher than their ADIs, simple distribution assessment was performed with food consumption data from a Chinese total diet study in 2012.ResultsThere are totally 21 food colorants have both ADI values and maximum use levels in GB 2760—2014. These 21 food colorants were included in the assessment by Budget method . The maximum theoretical daily intake of 15 food colorants exceeded their ADIs. Then, these 15 food colorants were assessed by simple distribution assessment. The result showed that the average intakes were below ADIs but the P95 intakes of 2 food colorants exceeded the ADIs in the whole population. Among consumers, the average intakes were also below ADIs, but the P95 intakes of 8 food colorants exceeded the ADIs.ConclusionThe health risks of most food colorant intakes in the national standard were at low levels. However, a few food colorants showed a requirement for further assessment with the actual concentrations in foods to confirm their health risk level.